A post-humanist and anti-capitalist understanding of the rights of nature (with a coda about the commons) - Luis Lloredo Alix (Oñati Socio-Legal Series)
I will raise the question of whether it is conceptually acceptable and practically useful to speak in terms of rights of Nature. I will answer positively: we may talk about rights of Nature with complete legitimacy. In addition, I will argue that we must do so from an anti-capitalist and postcolonial perspective; that is, not as a metaphor or a legal fiction, but considering that for some peoples of the world, natural entities genuinely have a personality worthy of protection through rights. I will also defend that the expression “rights of Nature” goes beyond the problem of the entitlement (Nature or Earth as “new holders”). Indeed, the emergence of the rights of Nature implies a radical change in the actual concept of rights; a change which compels us to move from humanism to post-humanism. This in turn leads us to dismantle the individualistic, anthropocentric, Eurocentric and ownership-based perspective of rights.